Hereditary hemochromatosis: cellular response to oxidative stress - Andrade, Lara Filipe Rocha (2018)
Iron is a key element for basic cellular functions. If iron homeostasis is not maintained it may lead to iron overload. Patients with Hereditary Hemochromatosis (HH) and with the C282Y HFE mutation have a progressive severe iron overload that, if it is not treated, may lead to tissue damage, that mostly culminate in hepatic cirrhosis and carcinoma. Having in mind that tissue damage in HH may be related with oxidative stress (OS) caused by iron toxicity, it is important to understand in what way the OS defense is acting in cells from HH patients with severe forms of iron overload. Few studies have been performed concerning the eventual prooxidant state in blood cells, which bear a major source of OS. Nevertheless, in a recent study it was shown that cultured lymphocytes (LY) from HH, when compared with cultured LY from controls and patients with secondary forms of hemochromatosis, have an increased protection against chromosome instability (CI) induced by 1,2:3,4 diepoxybutane (DEB) – an OS-related alkylating agent. This suggests an adaptive response of HH cells to the high level of OS. However, it is not known yet if the same response can be observed with other sources of iron toxicity, namely in the presence of bleomycin (BLM), that acts forming a complex with non-transferrin bound iron (NTBI). In order to better understand the oxidant status of HH blood cells and the putative adaptive response of HH cells to iron toxicity, a study was performed to characterize two selected OS parameters: evaluation of reduced glutathione (GSH) depletion and of lipid peroxidation (LPO). The study was performed in red blood cells (RBC) and lymphocytes (LY), either basal and after 36h in culture, with and without induction of OS. Induction of OS was performed with DEB and with BLM. A second objective of the present work was to test if the previously observed adaptive response of HH cells to DEB-induced OS can also be observed after induction with BLM. Characterization of the OS parameters was performed in RBC and LY from 5 HH patients with severe iron overload and 6 healthy donors (HD), at day 0 and after 36h of culture, non-treated and treated with DEB or BLM. Studies of CI were performed in BLM-induced LY from the same 5 HH patients and 6 HD. The results show that RBC from HH patients, compared with those from HD, have a larger GSH depletion and more LPO, either at day 0 and after 36h in culture medium. This suggests an increased level of OS in HH RBC. On the contrary, LY from HH patients present less GSH depletion after 36h of culture than LY from HD, being this effect more pronounced in DEB and BLM-treated cultures. Additionally, LPO levels were decreased in LY from HH patients after 36h of culture when compared with LY from HD. This result suggests that HH cultured LY, either non-treated or treated with DEB and BLM, have a still not completely understood mechanism of defense against OS. BLM-induced CI in cultured LY from HH patients was not different from the observed in cultured LY from HD. Therefore, we can postulate that toxicity induced by BLM did not increased CI in cells from HH patients with severe iron overload.